2008
DOI: 10.1371/journal.pmed.0050202
|View full text |Cite
|
Sign up to set email alerts
|

Faecal and Urinary Incontinence after Multimodality Treatment of Rectal Cancer

Abstract: Marilyne Lange and Cornelis van de Velde discuss the differential diagnosis and management of incontinence after rectal cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Interestingly, our analysis showed that, following sphinctersparing surgery, a statistically significant improvement of bowel continence compared to baseline occurred 3 years after surgery. Although this is in line with previous studies suggesting an improvement in anorectal function after 12 to 18 months from low anterior resection (46)(47)(48), we recommend caution when interpreting these results. Indeed, the absolute changes in the IS over time were especially small and, even if a statistically significant difference was found at 3 years, this may not necessarily reflect clinically relevant changes in bowel continence at this specific time point.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, our analysis showed that, following sphinctersparing surgery, a statistically significant improvement of bowel continence compared to baseline occurred 3 years after surgery. Although this is in line with previous studies suggesting an improvement in anorectal function after 12 to 18 months from low anterior resection (46)(47)(48), we recommend caution when interpreting these results. Indeed, the absolute changes in the IS over time were especially small and, even if a statistically significant difference was found at 3 years, this may not necessarily reflect clinically relevant changes in bowel continence at this specific time point.…”
Section: Discussionsupporting
confidence: 91%
“…Evidence‐based treatment guidelines are lacking for postsurgical incontinence in CRC survivors; thus, recommendations are based on interventions used in the general population. Kegel exercises can be helpful for stress incontinence due to pelvic floor dysfunction, but pelvic floor strengthening may be limited if denervation occurred during surgery . Other conservative therapies, such as dietary modification (limiting caffeine and fluid intake) or medications, may also be useful.…”
Section: Assessment and Management Of Physical And Psychosocial Long‐mentioning
confidence: 99%
“…Patients with LARS often rely on strategies such as the use of pads, self‐medication with laxatives and changes to diet in an attempt to control symptoms . Biofeedback can be used to help patients to improve evacuation or incontinence and is often the first‐line treatment option.…”
Section: Introductionmentioning
confidence: 99%